Emergence-urban fabric in the urban design of Ludovico Quaroni: morphology vs typology (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
The axiom of Ludovico Quaroni that forms the basis of his theories on the city, namely that ‘urban fabric’ can be regarded as being logically opposed to ‘emergence’, can be seen as one of his most significant areas of research both in his career as an architect and as a university teacher. All Quaroni’s urban projects, from his designs for the Città Nuove south of Rome, for La Martella, San Giusto in Prato and the Barene di San Giuliano in Venice, to the settlement of Il Gualdo in the Maremma and his researches on the residential Continuum, were based on the creation of complex residential fabrics whose guiding principle was sometimes an absolutely geometrical arrangement (San Giusto in Prato), but more often consisted of an unrestricted accumulation of volumes, open and closed spaces, light and shade, where the impressive richness of the various strata found in historical cities is replaced by skilfully arranged, seemingly random patterns (Il Gualdo and La Martella). In his work of creating continuous fabrics for modern cities, Quaroni rapidly set out to define the necessary relationship between typology and morphology, and with a natural facility and effortless mastery (‘sprezzatura’ in the Renaissance sense), he made use of all known types of materials (and attempted to update them).